The notion of "protracted armed conflict" in the Rome Statute and the termination of armed conflicts under international law: An analysis of select issues. (December 2019) - Lewis, Dustin A.
Abstract: Legal controversies and disagreements have arisen about the timing and duration of numerous contemporary armed conflicts, not least regarding how to discern precisely when those conflicts began and when they ended (if indeed they have ended). The existence of several long-running conflicts – some stretching across decades – and the corresponding suffering that they entail accentuate the stakes of these debates. To help shed light on some select aspects of the duration of contemporary wars, this article analyzes two sets of legal issues: first, the notion of "protracted armed conflict" as formulated in a war-crimes-related provision of the Rome Statute of the International Criminal Court, and second, the rules, principles and standards laid down in international humanitarian law and international criminal law pertaining to when armed conflicts have come to an end. The upshot of the analysis is that under existing international law, there is no general category of "protracted armed conflict"; that the question of whether to pursue such a category raises numerous challenges; and that several dimensions of the law concerning the end of armed conflict are unsettled.